Endogenous technology sharing in R&D intensive industries - Derek J. Clark; Jan Yngve Sand (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
This paper analyses endogenous formation of technology sharing coalitions with asymmetric firms. Coalition partners produce complementary technology advancements, although firms do not co-operate on R&D investment level or in the product market. The equilibrium coalition outcome is either between the two most efficient firms, or a coalition with all three firms. The two-firm coalition is the preferred outcome of a welfare maximising authority if ex ante marginal cost is sufficiently high, and the threefirm coalition is preferred otherwise. Furthermore, we show that the equilibrium outcomes result in the lowest total R&D investment of all possible outcomes. Aircraft engine manufacturing provides a case study, and indicates the importance of antitrust issues as an addition to the theory.
Keywords: L11; L13; 330; R&D; endogenous coalitions; asymmetric firms; Industrielle Forschung; Forschungskooperation; Koalition; Verhandlungstheorie; Forschungskosten; Wohlfahrtseffekt; Konzentrationspolitik; Flugzeugantrieb; Theorie; Welt